Ab initio calculations of collisional line–shape parameters and generalized spectroscopic cross-sections for rovibrational dipole lines in HD perturbed by He. (October 2020) - Stankiewicz, Kamil; Jóźwiak, Hubert; Gancewski, Maciej; Stolarczyk, Nikodem; Thibault, Franck; Wcisło, Piotr
Highlights: Close-coupling calculations of generalized spectroscopic cross-sections. Ab initio investigation of pressure broadening and shift coefficients. Ab initio investigation of Dicke parameters. Data for electric dipole R (j=0-5) and P (j=1-6) lines for purely rotational transitions, fundamental band and first four overtones. Abstract: We report ab initio calculations of generalized spectroscopic cross-sections for hydrogen deuteride perturbed by helium. From these calculations, collisional line-shape parameters are deduced for the HD electric dipole transitions: from R(0) to R(5) and from P(1) to P(6) in the 0–0 to 5–0 bands. These parameters are necessary for a proper interpretation of HD spectra from the atmospheres of gas giants. We demonstrate that the centrifugal distortion cannot be ignored, not only for pure rotational lines but also for rovibrational lines when one aims at sub–percent accuracy of the collisional line–shape parameters.